Crafting the customer experience for people not like you how to delight and engage the customers your competitors don't understand - McDonald, Kelly 1961- (John Wiley & Sons, 2013)
Deliver a better business experience, for every kind of customer A "one-size fits all" approach to customer service is no longer viable. Businesses competing on service need to understand and cater to customers' racial, ethnic, religious, generational, and geographic differences in order to meet or exceed customers' service expectations. Crafting the Customer Experience to People Not Like You shows how companies, brands, and products struggling to differentiate themselves in a sea of sameness can foster long-term loyalty and brand preference with exceptional and customized customer service.